2015
DOI: 10.1001/jama.2015.15553
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Cesarean Delivery Rate and Maternal and Neonatal Mortality

Abstract: National cesarean delivery rates of up to approximately 19 per 100 live births were associated with lower maternal or neonatal mortality among WHO member states. Previously recommended national target rates for cesarean deliveries may be too low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
386
6
7

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 485 publications
(410 citation statements)
references
References 19 publications
11
386
6
7
Order By: Relevance
“…A recent study demonstrated that a national CS rate of up to approximately 19 per 100 live births is associated with lower maternalor neonatalmortalityamong WHO member states [22]. It can be assumed that the previously recommended national targetratesfor CS deliveries may be too low.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study demonstrated that a national CS rate of up to approximately 19 per 100 live births is associated with lower maternalor neonatalmortalityamong WHO member states [22]. It can be assumed that the previously recommended national targetratesfor CS deliveries may be too low.…”
Section: Discussionmentioning
confidence: 99%
“…Higher CS delivery rates were not correlated with maternal or neonatal mortality at a country level in that study. A sensitivity analysis including only 76 countries demonstrated that delivery rates of >6.9 to 20.1 per 100 live births were inversely correlated with the MMR [22]. …”
Section: Discussionmentioning
confidence: 99%
“…The rate of cesarean delivery has increased dramatically worldwide over the past several decades and now exceeds 55% of all deliveries in many countries 1. In the US, cesarean section frequency has surpassed 30% for nearly a decade,2,3 with a wide distribution that ranges from 7.1% to 69.9% across hospitals 4.…”
Section: Introductionmentioning
confidence: 99%
“…Short-term complications include hemorrhage, pain, excessive use of pain medication, infection, damage to pelvic organs, and maternal mortality. Pelvic pain, emotional problems, and infertility are among the long-term complications of CS (5)(6)(7)(8)(9). The total rate of side effects after CS was estimated as 11.6% (10).…”
Section: Introductionmentioning
confidence: 99%